Open‐label Phase 3 Continuation Study of Cholic Acid in Patients With Inborn Errors of Bile Acid Synthesis - Heubi, James E.; Setchell, Kenneth D.R. (Journal of pediatric gastroenterology and nutrition, 2020)
ABSTRACT Background: In patients with bile acid synthesis disorders (BASD), impairment in the primary bile acid synthetic pathway leads to reduced primary bile acids, upregulated synthesis of cholesterol, and production and accumulation of hepatotoxic atypical bile acids. Primary bile acid therapy downregulates bile acid synthesis, reduces the production of hepatotoxic intermediates, and produces a functional bile acid pool fostering normal liver function. Methods: This phase 3, open‐label, single‐arm study included patients with BASD who had received cholic acid (10–15 mg · kg−1 · day−1) as part of a previous study, or were newly diagnosed. Efficacy assessments included urinary atypical bile acids; serum liver chemistries; body weight and height. Efficacy analyses compared baseline with worst postbaseline response (primary) or best postbaseline response (sensitivity). Treatment‐emergent adverse events (TEAEs) were summarized. Results: Of 53 total patients (single enzyme defects, n = 41; Zellweger spectrum disorders, n = 12), 22 (42%) were treatment‐naïve, and 31 (58%) were on cholic acid from a previous study. Mean age at diagnosis was 55 months, and at present study, baseline was 9 years. Using baseline‐to‐best postbaseline analyses, statistically significant improvements in urinary bile acids (P = 0.003), height (P < 0.001), and body weight (P < 0.001) were observed. Serum alanine aminotransferase and aspartate aminotransferase levels tended to decrease from baseline in treatment‐naïve patients following cholic acid treatment and remained stable in previously treated patients. Treatment‐naïve patients improved in all baseline‐to‐best postbaseline analyses. The most common TEAE was upper respiratory tract infection (17%). Conclusion: Oral cholic acid provides a safe and efficacious short‐ and long‐term therapy for patients with BASD.